A Comparison of The Official Tourism Website Effectiveness of Bali And North Sumatra Province: A Content Analysis Approach - Akbar, M Aulia; Wibowo, S. Kunto Adi; Fuady, Ikhsan (Institut Pariwisata Trisakti, 2022)
This study discusses the comparison of Bali and North Sumatra Tourism website in terms of website effectiveness. A content analysis method consisting of three dimensions, namely Aesthetics (Destination Visualisation and Web Design), Informative (Uniqueness and Cultural Promotion), and Interactive (E-travel planners and Online Communities), is used to analyze and assess tourism website both on the island of Bali and North Sumatra. The results is there are differences in the use of the Destination Visualisation Factor (AES1) and Web Design (AES2). Meanwhile other dimensions are no difference. This analysis can be used by tourism organizations to use the website better to promote and marketing tourism. Keywords: Content Analysis, Effectiveness, Tourism Website, Bali, North Sumatra